A new species of Selatosomus Stephens and the occurrence of Pristilophus melancholicus (Fabricius) in China (Coleoptera: Elateridae: Dendrometrinae) - Qiu, Lu (Zootaxa, 2018)
Selatosomus huanghaoi Qiu, new species is described from Yunnan, China. Habitus and diagnostic characters of the new species are illustrated. The presence of Pristilophus melancholicus (Fabricius) in China is confirmed.